2021
DOI: 10.3389/frvir.2021.707731
|View full text |Cite
|
Sign up to set email alerts
|

Using Ultrasonic Haptics Within an Immersive Spider Exposure Environment to Provide a Multi-Sensorial Experience

Abstract: A proof of concept virtual reality system is presented that integrates ultrasonic feedback sensations to provide a demonstrative virtual reality exposure therapy environment containing multiple scenarios with virtual spiders. This system and environment were utilised to conduct a study containing 35 participants with the goal of investigating the effect the environment could have on their level of anxiety. This level of anxiety was measured in three different forms: changes in frontal asymmetry analysis of EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The existence of gradual challenges, where each task is presented only when the user feels comfortable with the level of challenge offered in the previous task, promotes feelings of competence and contributes to a minimum ludic immersion potential. All studies classified as having low ludic immersion potential had some form of difficulty variation, either adaptively based on individual anxiety levels [81] or via predefined tasks and environments with different difficulty levels [60,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]82].…”
Section: Low Potential For Ludic Immersionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of gradual challenges, where each task is presented only when the user feels comfortable with the level of challenge offered in the previous task, promotes feelings of competence and contributes to a minimum ludic immersion potential. All studies classified as having low ludic immersion potential had some form of difficulty variation, either adaptively based on individual anxiety levels [81] or via predefined tasks and environments with different difficulty levels [60,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]82].…”
Section: Low Potential For Ludic Immersionmentioning
confidence: 99%
“…Although Farrell et al [67] and Minns et al [65] had high realism due to high-definition video captures of real environments and animals, they lacked sufficient navigational freedom as they were non-interactive videos that didn't allow users to explore the presented environment spatially. Brice et al [82] utilized a HMD capable of providing 6DOF; however, the freedom of movement was not explored in the study. The participants were seated during the VRE experimentation, and the extent of the space was confined to a box where the exposure stimuli were presented.…”
Section: Low Potential For Spatial Immersionmentioning
confidence: 99%
See 1 more Smart Citation
“…To that end, Brice et al created a mid-air haptically enhanced VR environment where users were exposed to virtual spiders (in jars, near them, or on their hands) and used EEG recordings and skin conductance levels to measure changes in anxiety and distress. Their results were then contrasted to self reported data obtained through the Fear of Spiders Questionnaire [84].…”
Section: Neuroscience Research Studiesmentioning
confidence: 99%
“…In clinical contexts, virtual reality has been used effectively to deliver exposure therapy, a treatment that depends on its ability to provoke fear and anxiety (see the meta-analysis by Wechsler et al, 2019). In nonclinical contexts, simulations that involve heights or threatening animals such as spiders (Brice et al, 2021) induce strong fear responses that include subjective feelings of fear, physiological changes consistent with activation of the sympathetic branch of the autonomic nervous system (e.g., increased heart rate [HR] and skin conductance; Gromer et al, 2019), and behavioral responses consistent with caution (Kisker et al, 2021). Interestingly, it has been repeatedly demonstrated that fear (or anxiety) experienced in virtual reality positively correlates with presence (Alsina-Jurnet et al, 2011; Bouchard et al, 2008; Ling et al, 2014; Peperkorn & Mühlberger, 2013; Peperkorn et al, 2015; Price & Anderson, 2007; Price et al, 2011; Riva et al, 2007; Robillard et al, 2003), leading some to propose that emotional experiences (fear, in particular) may be causally linked to presence (Price et al, 2011).…”
mentioning
confidence: 99%